Notes on frontier science: research on the edges? - Rosa María Medina Borges (Medisur, 2023)
The objective of this article is to assess the need to approach the knowledge of frontier science, as a transformative search alternative for today's complex problems. The reflection carried out focuses on the referent of complexity, with the approach of thinkers who, as confluences and dissents, are articulated in the awareness of the displacement of the enunciation, in the methodological field of current science. Reflections are offered on the contributions and limitations of modern science, the new scenarios of epistemological debate that are opening at the international level, from the urgencies of a collapsed world, immersed in the fourth technological revolution, but unable to solve the most urgent needs of life.